Effect of Kidney Volume on the Results of Nephrectomy Performed for Xanthogranulomatous Pyelonephritis - İLBEY, YUSUF ÖZLEM; Kisa, Erdem; Keskin, Mehmet Zeynel; Yucel, Cem; Yalbuzdag, Okan N.; Karabicak, Mustafa; Ilbey, YUSUF ÖZLEM (My University, 2019)
Aim